Schoenberg's twelve-tone harmony: The suite op.29 and the compositional sketches - Hyde, Martha M. (Michigan UMI research press, 1982)
This classic analysis of Schonberg's Suite Op. 29 is essntial for anybody concerned with atonal harmony, or the study of Schoenberg. This great study presents us with the ideas behind Schoenberg's use of the twelve-tone row, and how he achieved large-scale coherence and small-scale progression. The real value of this work is Hyde's work with Schoenberg's rhythmically devices and how Schoenberg maintained a certain harmonic rhythms to lay out his use of the row. This is a rare study in serial music and should be read by any serious scholar of the subject.